Fabrication of a Selective Sensor Amplification Probe Modified with Multi-Component Zn2SnO4/SnO2 Heterostructured Microparticles as a Robust Electrocatalyst for Electrochemical Detection of Antibacterial Drug Secnidazole - Ramaraj Sukanya (MDPI AG, 2021)
In this study, we synthesized heterostructured zinc stannate/tin oxide microparticles (ZTO/TO MPs) by a simple coprecipitation method and used them as an effective electrode material for the electrochemical detection of the antibacterial drug secnidazole (SCZ). The as-prepared ZTO/TO MPs were characterized by XRD, Raman, FE-SEM, HR-TEM, EDX, and XPS analyses. The physiochemical studies clearly proved that the fabricated ZTO/TO MPs were formed in a heterostructure phase without other impurities. A glassy carbon electrode modified with the synthesized ZTO/TO MPs showed an excellent and improved electrocatalytic activity in the electrochemical reduction of SCZ. Using differential pulse voltammetry (DPV), an impressive linear calibration range, extending from 0.01 to 193 μM, was observed, coupled with a detection limit of 0.0054 μM and a sensitivity of 0.055 μA/μM. In addition, the ZTO/TO MPs/GCE showed very good selectivity for the detection of SCZ in the presence of a number of biological, inorganic, and structurally related compounds. Finally, the ZTO/TO MPs/GCE was investigated for the analysis of SCZ in human blood serum samples. A very good recovery was obtained when spiking the blood serum with SCZ, highlighting the good applicability of the ZTO/TO MPs/GCE for the electrochemical analysis of SCZ in complex biological samples.